Characterization and Biodegradation Test of Palm Kernel Meal Galactomanan-Based Bioplastics with Succinic Acid-Polyvinyl Alcohol Cross-Linking Agent - Novelista Djaleha; Erwin Abdul Rahim; Nurhaeni; Ruslan; Ni Ketut Sumarni; Prismawiryanti (KOVALEN: Jurnal Riset Kimia, 2026)
Environmental pollution caused by non-biodegradable plastic waste has become a major global concern, prompting the development of eco-friendly alternative materials. Bioplastics derived from natural polymers are considered a promising solution due to their biodegradability and renewability. A study has been conducted on the manufacture of bioplastics from palm kernel meal galactomannan, with the addition of succinic acid and PVA, as an effort to reduce pollution caused by plastic waste. This study aims to determine the characteristics of bioplastics, including tensile strength, elongation, Young's modulus, chemical structure, and biodegradation. Bioplastics were obtained by mixing galactomannan, PVA, and variations of succinic acid (0, 0.1, 0.2, and 0.3 g). The results showed a tensile strength of 3.61–8.76 MPa, elongation of 260.83–432.92%, and Young's modulus of 1.21–2.49 MPa. FTIR analysis confirmed the presence of ester bonds, indicating cross-linking, while the biodegradation test showed that all samples were completely degraded within 1 day. The 0.10 g variation produced the best tensile strength, while the control had the most stable surface. This galactomannan-based bioplastic has the potential to be an alternative to conventional plastic due to its good mechanical properties and very rapid degradation.